1990
DOI: 10.1080/01496399008051840
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Acetaldehyde, Propionaldehyde, and Butyraldehyde on Silica Gel

Abstract: Adsorption isotherms of acetaldehyde, propionaldehyde, and butyraldehyde on Davison silica gel were determined gravimetrically at three temperatures. The isoteric heat of adsorption initially increased at low loading and then decreased monotonically with an increase in loading. The equilibrium adsorption data were successfully correlated by Polanyi's potential theory. The equilibrium data were also correlated with the Langmuir, BET, Freundlich, and the Hines et al. models. The Freundlich and the Hines et al. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The subsequent decrease in the values of heat of adsorption can be attributed to the heterogeneity of the surface and multilayer coverage. 45 It is expected that amine groups in chitosan will be homogeneous energetically and, therefore, a constant heat of adsorption should be obtained. However, the substrate perlite is not expected to be homogeneous energetically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent decrease in the values of heat of adsorption can be attributed to the heterogeneity of the surface and multilayer coverage. 45 It is expected that amine groups in chitosan will be homogeneous energetically and, therefore, a constant heat of adsorption should be obtained. However, the substrate perlite is not expected to be homogeneous energetically.…”
Section: Resultsmentioning
confidence: 99%
“…The initial increase in the heat of adsorption may be attributed to lateral interactions between the adsorbed Cd ions, which are known to form complex molecules on a solid surface. The subsequent decrease in the values of heat of adsorption can be attributed to the heterogeneity of the surface and multilayer coverage . It is expected that amine groups in chitosan will be homogeneous energetically and, therefore, a constant heat of adsorption should be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Hines and Ghosh (1993) [5] studied the competitive adsorption of propane-propylene mixture on silica gel, which revealed that silica gel has the greatest selectivity for propylene compared with molecular sieve 13X and activated carbon. Ghosh and Hines (1990) [6] obtained the adsorption equilibrium experiment data of acetaldehyde, propionaldehyde and butyraldehyde on silica gel respectively. Strøm-Tejsen et al (2008) [7] proved that the improvement of the indoor air quality has a certain effect when the silica gel wheel was used by investigating passengers' perception.…”
Section: Introductionmentioning
confidence: 99%